2022
DOI: 10.4209/aaqr.210282
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Status in Wuhan City during and One Year after the COVID-19 Lockdown

Abstract: Anthropogenic activities have been established to have severe adverse effects on air quality. Consequently, the nature of daily events, directly and indirectly, influences the nature of air pollution observed. This study focused on describing air quality one year after the Coronavirus (COVID-19) pandemic lockdown (since anthropogenic activities had resumed back to normal) in Wuhan.Using the independent t-test, the means of air quality index (AQI) and individual air pollutants concentration during the lockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…Contrary to the findings of this study, previous long-term studies found that air pollution rates increase with time [ 62 , 63 ], possibly due to the lockdown measures being applied for less time than was the case for Istanbul. To make a significant comparison [ 64 ], we need to analyze the next “without lockdown” period as 12 March 2022–30 June 2023 (after lockdowns).…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to the findings of this study, previous long-term studies found that air pollution rates increase with time [ 62 , 63 ], possibly due to the lockdown measures being applied for less time than was the case for Istanbul. To make a significant comparison [ 64 ], we need to analyze the next “without lockdown” period as 12 March 2022–30 June 2023 (after lockdowns).…”
Section: Resultscontrasting
confidence: 99%